Academic Achievement in Algebra of the Public High School Students in the New Normal - Diana B. Rodrigo; Alfredo D. Alave (Philippine Social Science Journal, 2021)
This study describes the academic achievement level in Algebra of the public secondary school students in the new normal as a whole and when grouped according to sex and parent's highest educational attainment. Utilizing descriptive-comparative and correlational designs, the academic achievement level, significant differences and relationships among the variables, and the perceived learning difficulties in Quadratic Functions were determined using mean, Mann-Whitney, Kruskal Wallis, Chi-square test of association, Spearman rank correlation, and frequency and percentage distribution. Results showed that the academic achievement level was low; no significant difference and relationship between sex and academic achievement level; there was a significant difference and relationship between parent's highest educational attainment and achievement level, and students' top difficulty is transforming quadratic functions into the form f(x)=[a(x-h)^2]+k. Therefore, Algebra teachers, school heads, and parents should take necessary interventions to address the problem.